KOMPARASI MODEL HIDROGRAF SATUAN TERUKUR DENGAN HIDROGRAF SATUAN SINTETIS (STUDI KASUS DAS TUKAD PAKERISAN) - Ayub Benny Kristianto; I Nyoman Norken; I Gusti Bagus Sila Dharma; Mawiti Infantri Yekti (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2019)
COMPARATIVE MODEL OF MEASURED UNIT HYDROGRAPH WITH SYNTHETIC UNIT HYDROGRAPH (CASE STUDY OF TUKAD PAKERISAN WATERSHED) ABSTRACT Several methods and models of Synthetic Unit Hydrograph (SUH) have been developed to assist in the process of hydrological analysis within a Watershed. These methods include Snyder, Nakayasu, GAMA I, Limantara and ITB. The SUH methods are widely used by practitioners in calculating flood discharge, without knowing the deviations of these methods when compared to measured unit hydrographs in a watershed. This causes the SUH models give an overestimated or underestimated results to the measured unit hydrograph. Therefore, comparative SUH models are needed to determine the deviation of each model, and if necessary adjust the coefficient of the SUH model so that the SUH model approached the measured unit hydrograph in a watershed. Comparative studies of several SUH and measured unit hydrograph were performed on the Tukad Pakerisan watershed in Gianyar Regency-Bali. The measurable unit hydrograph comparisons on the watershed with the SUH Snyder, Nakayasu, GAMA I, Limantara, ITB-1 and ITB-2 models have significantly deviated results. This deviation is shown in three unit hydrograph parameters which include peak discharge (Qp), peak time (Tp), and base time (Tb). The SUH Snyder model with adjustment coefficient Ct = 0.800 and Cp = 1.052 very close to measured unit hydrograph of Tukad Pekerisan watershed with deviation less than 5%.